The Role of Higher Education in Developing Students' Entrepreneurial Intentions - Krystyna Buchta; Monika Jakubiak; Małgorzata Skiert; Maria Anna Turosz (Jesuit University Ignatianum in Krakow, 2016)
Entrepreneurship constitutes one of the key competences and a significant element of todays' university graduates' professional training. Academia, in its didactic and educational process, offers numerous opportunities for shaping students' entrepreneurial behaviours. A fundamental role in this respect is played by the scope of knowledge and skills offered, as well as by shaping proper attitudes in the course of professional internships, participation in student organisations and science club projects. The present study attempts to evaluate the university's role in the process of shaping entrepreneurial attitudes of students representing the selected universities in Lublin. Respondents' opinions, collected by means of a diagnostic poll method and a survey, were analysed. The paper verified the thesis regarding insufficient outcomes of education in developing entrepreneurial competences of students from selected universities.